2020
DOI: 10.2147/ijn.s245300
|View full text |Cite
|
Sign up to set email alerts
|

<p>Liposomal Encapsulated Curcumin Effectively Attenuates Neuroinflammatory and Reactive Astrogliosis Reactions in Glia Cells and Organotypic Brain Slices</p>

Abstract: Introduction: The polyphenolic spice and food coloring ingredient curcumin has beneficial effects in a broad variety of inflammatory diseases. Amongst them, curcumin has been shown to attenuate microglia reaction and prevent from glial scar formation in spinal cord and brain injuries. Methods: We developed a protocol for the efficient encapsulation of curcumin as a model for anti-inflammatory drugs yielding long-term stable, non-toxic liposomes with favorable physicochemical properties. Subsequently, we evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…A derivative of the South Asian turmeric plant rhizome, Curcuma longa (turmeric), the polyphenol curcumin has amassed quite a reputation in nutraceutical development for various diseases, including cancer and inflammatory conditions [34]. The healing properties of this yellow spice date back to ancient civilizations, featuring strongly in Ayurvedic therapy.…”
Section: Nano-phytopharmaceuticals In Neurological (Cns) Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…A derivative of the South Asian turmeric plant rhizome, Curcuma longa (turmeric), the polyphenol curcumin has amassed quite a reputation in nutraceutical development for various diseases, including cancer and inflammatory conditions [34]. The healing properties of this yellow spice date back to ancient civilizations, featuring strongly in Ayurvedic therapy.…”
Section: Nano-phytopharmaceuticals In Neurological (Cns) Disordersmentioning
confidence: 99%
“…In a glioblastoma study, Schmitt et al demonstrated that curcumin encased in liposomal carriers (LipoCur) proved to be superior in reducing the proliferation and reactivity of human microglia and astrocytes (human fetal astrocyte cell line, SVGA) compared to the free compound. Immunostaining of murine organotypic brain segments challenged with lipopolysaccharide (LPS) for eight days, revealed that LipoCur was equally effective in reducing glial scarring [34].…”
Section: Nano-phytopharmaceuticals In Neurological (Cns) Disordersmentioning
confidence: 99%
“…Since dipalmitoyl phosphatidylcholine (DPPC) was the most pH-stable liposome found, with a sustained drug release at physiological pH ( Yaroslavov et al, 2015 ), DPPC was selected as the carrier of curcumin to explore the therapeutic effect in human fetal astrocyte cell line SVGA model of neuroinflammation and reactive astrogliosis. Compared with free curcumin, LipoCur showed a significant downregulation of glial cell proliferation genes and a lower level of pro-inflammatory cytokines including IL-6, IL-1β, TGF-β, and TNF-α ( Schmitt et al, 2020 ). In addition, Cyclosporine A (CsA) in liposomal formulation (Lipo-CsA) inhibits the inflammation response, including myeloperoxidase (MPO) activity and TNF-α levels, in the model of ischemia reperfusion injury (I/R) cerebral injuries ( Partoazar et al, 2017 ).…”
Section: Organic Npsmentioning
confidence: 99%
“…62 Curcumin protects the white matter after SCI through inhibition of the NF-κB signaling pathway and activation of Nrf2 signaling by regulating ARE-driven antioxidant genes, such as HO-1. 21,63 It is worth noting that HO-1 activity can lead to inhibition of NF-κB-mediated transcription through the action of bilirubin by decreasing free intracellular iron ions. 64,65 Singh et al 66 reported the lack of TNF-α dependent phosphorylation and degradation of IκBα as well as the inhibition of translocation of the p65 subunit to the nucleus in curcumin-treated cells.…”
Section: Curcumin Protects Against Sci By Scavenging Free Radicals Through the Nrf2/ho-1 Signaling Pathwaymentioning
confidence: 99%